2016
DOI: 10.1080/09507116.2016.1142183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a constricted nozzle on the arc phenomena in the TIG welding process

Abstract: Figure 1 is a schematic of the computation model for TIG welding with a constricted nozzle attached. Since, however, in the actual computation model, the arc length is very much smaller than the horizontal dimension of the domain, Figure 1 is drawn so that the domain is readily comprehensible and is not to scale. The computational model, which assumed axial symmetry of the two-dimensional cylindrical coordinate system, comprised the tungsten electrode, gas nozzle, constricted nozzle and base metal. The dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In a paper by Konishi et al, the influence of the constricted nozzle was discussed using numerical simulation in the case of 3 mm arc length [13] with an anode of water-cooled copper. The results showed that, in comparison to the conventional TIG welding process, the heat flux on the anode surface was increased.…”
Section: Introductionmentioning
confidence: 99%
“…In a paper by Konishi et al, the influence of the constricted nozzle was discussed using numerical simulation in the case of 3 mm arc length [13] with an anode of water-cooled copper. The results showed that, in comparison to the conventional TIG welding process, the heat flux on the anode surface was increased.…”
Section: Introductionmentioning
confidence: 99%